Synthesis of Polyampholyte Janus‐like Microgels by Coacervation of Reactive Precursors in Precipitation Polymerization. (10th December 2019) - Xu, Wenjing; Rudov, Andrey; Oppermann, Alex; Wypysek, Sarah; Kather, Michael; Schroeder, Ricarda; Richtering, Walter; Potemkin, Igor I.; Wöll, Dominik; Pich, Andrij
Abstract: Controlling the distribution of ionizable groups of opposite charge in microgels is an extremely challenging task, which could open new pathways to design a new generation of stimuli‐responsive colloids. Herein, we report a straightforward approach for the synthesis of polyampholyte Janus‐like microgels, where ionizable groups of opposite charge are located on different sides of the colloidal network. This synthesis approach is based on the controlled self‐assembly of growing polyelectrolyte microgel precursors during the precipitation polymerization process. We confirmed the morphology of polyampholyte Janus‐like microgels and demonstrate that they are capable of responding quickly to changes in both pH and temperature in aqueous solutions. Abstract : Janus‐artige Polyampholyt‐Mikrogele wurden durch elektrostatisch angetriebene Selbstassemblierung und Koazervierung von wachsenden, entgegengesetzt geladenen Mikrogel‐Vorläufern während einer Fällungspolymerisation hergestellt. Dies ermöglicht die Entwicklung von neuen Wirkstoffträgern, umschaltbaren Emulsions‐Stabilisatoren und anpassungsfähigen Katalysatorträgern.